Ion‐channel degeneracy: Multiple ion channels heterogeneously regulate intrinsic physiology of rat hippocampal granule cells - Mishra, Poonam; Narayanan, Rishikesh (Physiological reports, 2021)
Degeneracy, the ability of multiple structural components to elicit the same characteristic functional properties, constitutes an elegant mechanism for achieving biological robustness. In this study, we sought electrophysiological signatures for the expression of ion‐channel degeneracy in the emergence of intrinsic properties of rat hippocampal granule cells. We measured the impact of four different ion‐channel subtypes—hyperpolarization‐activated cyclic‐nucleotide‐gated (HCN), barium‐sensitive inward rectifier potassium (Kir), tertiapin‐Q‐sensitive inward rectifier potassium, and persistent sodium (NaP) channels—on 21 functional measurements employing pharmacological agents, and report electrophysiological data on two characteristic signatures for the expression of ion‐channel degeneracy in granule cells. First, the blockade of a specific ion‐channel subtype altered several, but not all, functional measurements. Furthermore, any given functional measurement was altered by the blockade of many, but not all, ion‐channel subtypes. Second, the impact of blocking each ion‐channel subtype manifested neuron‐to‐neuron variability in the quantum of changes in the electrophysiological measurements. Specifically, we found that blocking HCN or Ba‐sensitive Kir channels enhanced action potential firing rate, but blockade of NaP channels reduced firing rate of granule cells. Subthreshold measures of granule cell intrinsic excitability (input resistance, temporal summation, and impedance amplitude) were enhanced by blockade of HCN or Ba‐sensitive Kir channels, but were not significantly altered by NaP channel blockade. We confirmed that the HCN and Ba‐sensitive Kir channels independently altered sub‐ and suprathreshold properties of granule cells through sequential application of pharmacological agents that blocked these channels. Finally, we found that none of the sub‐ or suprathreshold measurements of granule cells were significantly altered upon treatment with tertiapin‐Q. Together, the heterogeneous many‐to‐many mapping between ion channels and single‐neuron intrinsic properties emphasizes the need to account for ion‐channel degeneracy in cellular‐ and network‐scale physiology.